(untitled) (Филологические заметки, 2019)
The article problematizes the Croatian postmodern narrators’ share in a theoretical perception from the end of the 80’s. The relationship between theory and fiction is being analyzed on the modal narrative relations between the matter-offactness and narration, i.e. a possible world. That’s why the problem of verity is one of the substratum on which the narrators construct their books, whether it is a novel or a short story. The idea of virtuality intrudes itself upon a theory of possible worlds, essentially, so thus in Božek, Boban, Budiša and Gregorić.